Carlos Ramos Núñez. Towards a Latin American vision of law and literature studies - Jiménez Moreno, Manuel de J. (2022)
This essay reviews the theoretical-methodological contributions of Carlos Ramos Núñez, university professor and constitutional magistrate, in the field of interdisciplinary studies of law and literature. Although the author takes as a basis the classical model elaborated by American and European jurists. He makes a significant contribution by dealing in a special way with the «reconstruction and discussion of famous cases». This particular vision reflects his training as a legal historian and his affinities in favor of a cultural analysis of the legal phenomenon. This is undoubtedly necessary for the gradual construction of a Latin American identity in law and literature studies to strengthen the movement at the regional level.